Regulação das células da granulosa bovina por efetor da via de sinalização Hippo - Andrade, Leonardo Guedes de (2021)
Follicular growth in mammals is a complex and dynamic event that requires an interaction of different molecules and cell signaling pathways. In cattle, mainly granulosa cells undergo fundamental morphophysiological differentiations for the synthesis of 17β-estradiol (E2), through the expression of cytochrome P450 family 19 subfamily A member 1 (CYP19A1). The Hippo signaling pathway regulates tecidual homeostasis controlling the balance between proliferation and apoptosis. The effector YAP1 controls the transcription of proliferative and anti-apoptotic genes by interacting with transcription factors of the TEA domain family member (TEAD); among the target genes of YAP1, we are particularly interested in the connective tissue growth factor (CTGF). In the present work, we seek to understand how YAP1 regulation occurs, mainly under FSH stimulation, during the follicular divergence process. To accomplish this aim we use a culture of granulosa cells that mimics physiological aspects (in vitro) and also granulosa cells of ovariectomized animals (in vivo). Our results show that FSH appears to increase YAP1 phosphorylation, allowing cell differentiation to occur. In addition, when YAP1 inhibitors were added to the granulosa cell culture, there was an increase in CYP19A1 expression. Therefore, we suggest that the levels of phosphorylated YAP1 will increase as follicular dominance is established.